Our way(s) to action research: Doctoral students' international and interdisciplinary collective memory work. Issue 3 (September 2014) - Zhang, Zheng; Fyn, Dawn; Langelotz, Lill; Lönngren, Johanna; McCorquodale, Lisa; Nehez, Jaana
This study involved six Swedish and Canadian doctoral students who shared interests in using action research in professional education in different disciplines. We employed Noffke's three dimensions of action research as a theoretical framework (i.e., the Professional, the Personal, and the Political). Using collective biography as a methodology, we cooperatively examined how our personal and professional agendas and macro-level structures have been shaping our intentions to conduct action research projects in our respective disciplines. The key findings of this international and interdisciplinary collective biography relate our growing awareness of the intimacy between research and life in various professional and geographic contexts. Collectively addressing our shared frustrations, we celebrated action research as a methodology that attends to the dynamic and concrete lived experiences of our participants in various spatio-temporalities. Reflecting upon the hybridity of our own researcher identities, we were also able to see the intimate relation between ourselves as active citizens and critical action researchers who are determined to take up the challenges and engage in critically oriented action research that could nurture more "caring, " "empowering, " and "transforming" public spheres.